Keep calm and carry on - a systematic review of the literature on organizational crisis communication - Martins , Helena; Loureiro, Rui; Piedade, Lúcia (Conferência - Investigação e Intervenção em Recursos Humanos, 2023)
Organizational communication is a dynamic and rapidly evolving field that covers a wide range of topics. Some of the hot topics in the field of organizational communication currently include: digital transformation and communication, remote work and communication, cross-cultural communication, leadership communication and crisis communication. Crisis communication is a field that seems to be acquiring new relevance as challenges such as rapid technological changes, the climate crisis, geopolitical instabilities and pandemics, as well as other possible events may present added challenges for organizations. Crisis communication is the process of managing communication during a crisis situation. A crisis can take many forms, such as a natural disaster, a pandemic, a financial crisis, or a data breach, and it can have significant impacts on an organization and its stakeholders. Effective crisis communication is critical to managing the situation and minimizing its impact. This paper proposes a systematic review of the organizational crisis communication literature, using VosViewer software to map out the most significant themes and topics in the literature. Results are discussed in light of the main findings, generating a framework that mirrors a novel perspective regarding the topics most addressed in this field. Implocations for practice as well as research are discussed.